Single-cell RNA sequencing depicts metabolic changes in children with aplastic anemia - Zhou, Qin; Huang, Lifen; Liu, Yong; Huang, Junbin; Wen, Luping; Yang, Jing; Liang, Jintang; Chen, Yun; Chen, Chun (Frontiers in Oncology, 2023)
Aplastic anemia is bone marrow hematopoietic failure syndrome mediated by immune cells. The mechanism of immune disorder is not well understood and therapeutic strategies still need to be improved. Studies have found that abnormalities in metabolisms promote the survival of AA cells. In recent years, an increasing number of studies have reported the immunosuppressive therapy for the treatment of AA. In this study, we analyzed the transcriptome of AA from peripheral blood compared with healthy donors by single cell sequencing and identified the affected metabolic pathways including the lysine degradation. We demonstrated that the metabolic abnormalities of T lymphocytes mainly focus on glycolysis/gluconeogenesis. In addition, the metabolic abnormalities of natural killer cells concentrated in oxidative phosphorylation. The key genes involved in abnormal metabolic processes were NENF, INPP4B, AKR1C3 and CHST2 by differential gene expression analysis. Molecule interactions analysis showed that TNFSF12 in TNF signaling was broadly activated in AA. In conclusion, we suppose that the treatment of immune cells abnormal metabolic pathway may contribute to the development of novel strategies to treat AA.